1999
DOI: 10.1002/(sici)1096-8628(19990402)83:4<313::aid-ajmg15>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Fragile X syndrome and selective mutism

Abstract: This is the first report that details an association between fragile X syndrome (FXS) and selective mutism (SM). This 12-year-old girl with heterozygous full mutation at FMR1 has a long history of social anxiety and shyness in addition to SM. Her sister also has the full mutation and a history of SM that resolved in adolescence. A beneficial response to fluoxetine and psychotherapy is described. The FMR1 mutation appears to be the first gene mutation associated with SM and further studies are recommended to as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
3

Year Published

1999
1999
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(9 citation statements)
references
References 30 publications
0
6
0
3
Order By: Relevance
“…FXS patients exhibit hyper-reactivity to visual, olfactory, tactile and auditory stimulation [1], [66][69]. This hypersensitivity phenotype is manifested as AGS in Fmr1 KO mice [20].…”
Section: Discussionmentioning
confidence: 99%
“…FXS patients exhibit hyper-reactivity to visual, olfactory, tactile and auditory stimulation [1], [66][69]. This hypersensitivity phenotype is manifested as AGS in Fmr1 KO mice [20].…”
Section: Discussionmentioning
confidence: 99%
“…Of note, the effect of VPA on reactivation of the FMR1 gene in other types of tissue may be varied and still remains unclear. In addition, VPA has already been proven to be an effective treatment of behavioral and psychiatric symptoms in patients with autism or FXS (Sovner, 1989;Hagerman et al, 1999;Torrioli et al, 2010). For these reasons, using VPA to treat FXS cannot be excluded, although further research on its basic mechanisms is needed.…”
Section: F Fxsmentioning
confidence: 99%
“…Studies have suggested that fluoxetine may be beneficial to individuals with autism (Hollander et al, 2005, 2012; Kolevzon et al, 2006). Treatment with fluoxetine has shown some effect in fragile X mice and patients (Hagerman et al, 1999; Uutela et al, 2014). However, fluoxetine has some possible side effects in clinic, such as mood changes, agitation, restlessness, and aggression, and may not be suitable to all individuals with fragile X syndrome and other ASDs (Wernicke, 2004; Kolevzon et al, 2006; Uutela et al, 2014).…”
Section: Targeted Pharmacotherapy For Fragile X Syndromementioning
confidence: 99%